A "tilt" toward cinefluoroscopy. Issue 1 (11th December 2017) - Lampropoulos, Konstantinos; Bakalakos, Athanasios; Bazoukis, George; Saplaouras, Athanasios; Sakellaropoulou, Antigoni; Anagnostou, Aikaterini; Tse, Gary; Tsamatsoulis, Michalis; Charitos, Christos
Key Clinical Message: Fluoroscopy permits rapid and straightforward assessment of mechanical valve function and allows a distinction between normal and malfunctional prostheses, acting as a complementary diagnostic step. Abstract : Fluoroscopy permits rapid and straightforward assessment of mechanical valve function and allows a distinction between normal and malfunctional prostheses, acting as a complementary diagnostic step.